Engagement and time perception in virtual reality. (September 2021) - Read, Tyler; Sanchez, Christopher A.; De Amicis, Raffaele
Virtual reality (VR) is a simulation tool that is being used extensively to study the effects of training and perception. However, several studies have shown that some aspects of perception within VR are not always accurate. The present study investigates the perception of time within a VR environment by asking for retrospective time judgments of the length of VR experiences. These environments varied in both the level of interaction with the VR environment, and also the spatial properties of the environment itself. The judged length of time did not significantly differ between conditions based on the level of activity in the environment. However, the spatial properties of the VR environment did produce significantly different time estimations. This finding suggests that careful attention should be paid to what and how users are trained or evaluated in VR.